High prevalence of systemic disease and mortality in Asian subjects with systemic lupus erythematosus. Issue 7 (July 1991) - Samanta, A; Feehally, J; Roy, S; Nichol, F E; Sheldon, P J; Walls, J
Abstract : All patients with systemic lupus erythematosus (SLE) (American Rheumatism Association criteria with positive antinuclear antibody titre) and who attended any of the three general hospitals in Leicester over a 10 year period were ascertained using several complementary sources. Eighty seven subjects (26 Asian, 61 white) were identified. The estimated prevalence of SLE in Leicester is 0.4/1000 for Asian and 0.2/1000 for white subjects. Mean age of onset of the disease was 24 years in Asian and 31 years in white subjects, with both groups showing a female preponderance. Proteinuria (greater than 1 g/24 h) was noted in 15 (58%) Asian and 21 (35%) white subjects; neuropsychiatric disease in 10 (38%) Asian and 8 (13%) white subjects; myalgic symptoms with raised muscle enzymes in 9 (35%) Asian and 3 (5%) white subjects. Nineteen (73%) Asian subjects were positive for extractable nuclear antigens as well, at some stage of their disease, compared with 6 (10%) white subjects. Immunosuppressive treatment was required in 12 (46%) Asian and 12 (20%) white subjects, and deaths of seven Asian and five white subjects were attributed to SLE. These findings show that Asian subjects have a higher prevalence of SLE with greater systemic disease and mortality.